Navigating career paths: The role of socio-demographics in vocational education outcomes among Yoruba ethnic group - Paramole, Oyeronke Christiana; Adeoye, Moses Adeleke (INVOTEC, 2024)
This study examines the relationship between socio-demographic factors and vocational education outcomes among the Yoruba ethnic group in Nigeria. It highlights the importance of understanding how factors such as age, gender, socioeconomic status, educational background, and geographical location influence educational attainment and career choices within this demographic. The research uses qualitative interviews to gather data from a diverse sample of Yoruba participants. Key findings show that socio-demographic characteristics significantly affect participants' access to vocational education and their career outcomes. Younger individuals and those from higher socioeconomic backgrounds are more likely to enroll in advanced vocational training programs while older participants face challenges due to limited opportunities and resources. Gender disparities also emerge, with women often encountering cultural and societal barriers that hinder their participation in certain vocational fields. Geographical factors also play a critical role with urban residents having greater access to quality vocational training institutions than rural ones. The study advocates for inclusive policies that cater to the diverse needs of the Yoruba population, aiming to enhance vocational education outcomes and promote sustainable career paths.